1997
DOI: 10.1063/1.118773
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial characteristics of N2O and NO nitrided SiO2 grown on SiC by rapid thermal processing

Abstract: Interfacial characteristics of Al/SiO2/n-type 6H–SiC metal–oxide–semiconductor capacitors fabricated by rapid thermal processing (RTP) with N2O and NO annealing are investigated. Interface state density was measured by a conductance technique at room temperature. RTP oxidation in pure O2 leads to an excellent SiO2/n-type 6H–SiC interface with interface state density in the order of 1010–1011 eV−1 cm−2. NO annealing improves the SiO2/n-type 6H–SiC interface, while N2O annealing increases the interface state den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
182
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 314 publications
(186 citation statements)
references
References 19 publications
3
182
0
1
Order By: Relevance
“…We have observed that, for dry oxides, wet oxides, thin oxides (~ 40nm) and thick oxides (80nm), our optimized NO passivation process results in an interface state density of around 2x10 12 cm -2 eV -1 for n-4H-SiC at E c -E = 0.1eV. This interface state density may be compared to a trap density of approximately 10 10 cm -2 eV -1 for passivated Si/SiO 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have observed that, for dry oxides, wet oxides, thin oxides (~ 40nm) and thick oxides (80nm), our optimized NO passivation process results in an interface state density of around 2x10 12 cm -2 eV -1 for n-4H-SiC at E c -E = 0.1eV. This interface state density may be compared to a trap density of approximately 10 10 cm -2 eV -1 for passivated Si/SiO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [12] reported improvements in the interface characteristics of 6H-SiC MOS capacitors following high temperature anneals in nitric oxide (NO). We have applied similar techniques to 4H-SiC to develop a passivation process that reduces the interface state density near the conduction band edge by more than one order of magnitude for n-4H-SiC MOS capacitors [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first experiments on nitridation of oxides on SiC were presented by Li et al [126], who observed a reduction of the interface state density at SiO 2 /6H-SiC interfaces after an annealing in NO, with respect to a rapid thermal oxidation process in O 2 . The beneficial impact of the NO process on the interface state density was generically attributed to a reaction of nitrogen with the silicon dangling bonds during the oxidation.…”
Section: Interface Transport Properties In the Sio 2 /Sic Systemmentioning
confidence: 99%